Effect of Activated Charcoal on Some Phenolic Compounds of Apple Juice - Ekinci, Raci (Asian Journal of Chemistry, 2012)
The effect of activated charcoal on the content of several phenolic compounds in apple juice has been studied. In this study, 0, 0.5, 1.0, 2.0 and 3.0 g/L amounts of activated charcoal were added into apple juice. Apple juice samples were then shaken gently for 0, 5, 10, 20 and 30 min, respectively. The quantitative analysis of phenolic compounds using high-performance liquid chromatography with diode-array detection was carried out. Considerable reduction in the content of phenolic compounds (gallic acid, chlorogenic acid, caffeic acid, p-cumaric acid, quercetin, phloridzin, (+)-catechin, catechol, (-)-epicatechin and protocatechuic acid) of apple juice was found. The highest decrement in the content of phenolic compounds was obtained at 3.0 g/L activated charcoal mixed for 5 min. The length of mixing period did not seem to have any more effect on the content of phenolic compounds of apple juice.